2016
DOI: 10.5027/andgeov43n2-a05
|View full text |Cite
|
Sign up to set email alerts
|

Temporal seismic wave velocity variations at Láscar volcano

Abstract: ABSTRACT. We report on the first study using Seismic Wave Interferometry to determine variations of seismic velocities through time, in the vicinity of Láscar volcano in Chile. Seismic Wave Interferometry has been used as a powerful tool to determine spatial and temporal changes of seismic velocities within the Earth. Spatial variations of seismic velocities are related to heterogeneities of material properties, which are expected to occur in a complex structure. However, temporal changes are indicative of dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Despite the difficulty of forecasting steam-driven explosions, some studies have retrospectively identified unexpected precursor activity associated with Lascar's episodes of unrest. Wooster (2001) described the new rapid cooling behaviour of the Lascar dome as precursor activity following the 1993 eruption, while a recent study of the 2013 explosion utilized seismic wave interferometry to depict variations in the seismic velocity and consequently speculated on the pre-eruptive deformation of a magmatic/hydrothermal reservoir (González et al, 2016). Matthews et al (1997) proposed a continuous deepening of the crater floor associated with a high rate of degassing from fumaroles within the active crater; this degassing phenomenon was subsequently identified by an InSAR investigation (Pavez et al, 2006) and further confirmed by continuous monitoring using the high-resolution German satellite TerraSAR-X (Richter et al, 2018), which also showed that the deformation rate appeared to be largely unaffected by the most recent explosive eruptions in 2013 and 2015.…”
Section: Study Area and Explosive History Of Lascar Volcanomentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the difficulty of forecasting steam-driven explosions, some studies have retrospectively identified unexpected precursor activity associated with Lascar's episodes of unrest. Wooster (2001) described the new rapid cooling behaviour of the Lascar dome as precursor activity following the 1993 eruption, while a recent study of the 2013 explosion utilized seismic wave interferometry to depict variations in the seismic velocity and consequently speculated on the pre-eruptive deformation of a magmatic/hydrothermal reservoir (González et al, 2016). Matthews et al (1997) proposed a continuous deepening of the crater floor associated with a high rate of degassing from fumaroles within the active crater; this degassing phenomenon was subsequently identified by an InSAR investigation (Pavez et al, 2006) and further confirmed by continuous monitoring using the high-resolution German satellite TerraSAR-X (Richter et al, 2018), which also showed that the deformation rate appeared to be largely unaffected by the most recent explosive eruptions in 2013 and 2015.…”
Section: Study Area and Explosive History Of Lascar Volcanomentioning
confidence: 99%
“…A shallow hydrothermal system depicted by magnetotelluric and seismic data (Díaz et al, 2012;Hellweg, 2000) seems to influence the active degassing at Lascar (Bredemeyer et al, 2018;Tassi et al, 2009). These degassing processes have been suggested to be the source of the tremors observed during the 1994-1995 period of unrest (Hellweg, 2000), and they are probably associated with the increase in longperiod (LP) events preceding an eruption (González et al, 2016).…”
Section: Study Area and Explosive History Of Lascar Volcanomentioning
confidence: 99%
“…Additionally, a magnetotelluric study (Díaz et al 2012) imaged a high-conductivity volume at only ∼1 km beneath the summit, suggesting the presence of a shallow hydrothermal system; Díaz et al (2012) further identified an anomaly at a depth of 6 km, which could be associated with a magma storage zone. Seismic wave interferometry allowed some scholars to speculate on the seismic velocity variations associated with inflation/deflation processes in a magmatic or hydrothermal reservoir during the period of unrest preceding the 2013 eruption (González et al 2016). This velocity variation also coincided with an increase in the number of LPs, an intensification of fumarole degassing, and the phenomenon of crater incandescence.…”
mentioning
confidence: 99%